Pengaruh Profitabilitas, Leverage, Growth Opportunity, dan Kebijakan Dividen Terhadap Nilai Perusahaan pada Perusahaan yang Terdaftar di LQ45 Periode 2021-2024 (Lembaga Pengembangan Kinerja Dosen, 2025)
This research is motivated by the importance of company value as an indicator that reflects market perception of the performance prospects of a business entity. For companies included in the LQ45 index, company value reflects investor confidence in long-term sustainability and growth. This study aims to analyze the effect of profitability, leverage, growth opportunities, and dividend policy on company value in companies included in the LQ45 index during the 2021–2024 period. The study uses a quantitative approach with secondary data from annual financial reports. The sampling technique used purposive sampling, with a total of 16 companies in the 4-year study, resulting in 64 observations. The analysis was conducted using panel data regression with a Fixed Effect Model approach through STATA 14 Software. The results show that leverage and growth opportunities have a significant effect on company value. Profitability and dividend policy do not have a significant effect on company value. Simultaneously, all four variables have a significant effect on company value. These findings indicate that capital structure and growth prospects are important factors in increasing company value.